Diagnosis and treatment challenges of autism spectrum disorder at a reference hospital in Douala, Cameroon - Daniele Christiane Kedy Koum; Dominique Enyama; Loick Pradel Kojom Foko; Diomede Noukeu; Belviane Nguedia; Rhita Mbono; Charlotte Eposse; Patricia Epee Eboumbou; Cathy Bebey Engome; Yacouba Njankouo Mapoure (BMC, 2023)
Abstract Background Autism spectrum disorder (ASD) is a neurodevelopmental disability associated with deficiency in social interaction, unusual development of social communication, and restricted or repetitive behaviors, interests and activities. This study aimed to describe management of pediatric ASD in Cameroon, a resource-constrained Central Africa country. Methods A retrospective study was conducted between December 2021 and May 2022 at the Pediatrics department of a reference hospital in the town of Douala. Data of interest of children with ASD were collected through eligible medical records and telephone discussions with their parents/guardians. Results Medical records of 145 children with ASD aged 2-15 years were included in the study, giving a hospital ASD prevalence of 3.7%. Time delay between parental concerns and hospital management was specified in 69 (47.58%) children, and among them 38 (55.07%) had a mean delay ± SD was less than five months. Children were mainly males (76%) and aged 4-5 years (37.93%), with mean age ± SD of 44.4 ± 22.2 months old. The main consultation reason was delayed language development (100%). Mean time delay between parental concerns and the first medical consultation was 18 months (range 1-60 month). Attention deficit hyperactivity disorder were found in 68.18% of children aged ≥ 6 years old. Neuropsychology (66.2%) was the most frequently used intervention. Some children were treated using traditional medicine. Conclusions Management of pediatric ASD is strongly influenced by socioeconomic and cultural context. It is crucial to implement behavioral change campaigns in community, organize training sessions to medical staff on diagnosis and treatment of ASD, and provide specialized centers with skilled staff and equipped material.